Commodity price volatility and inclusive growth in low-income countries - Arezki, Rabah; Quintyn, Marc; Pattillo, Catherine A. (Catherine Anne); Zhu, Min, 1952- (International Monetary Fund, 2012)
In the years following the global financial crisis, many low-income countries experienced rapid recovery and strong economic growth. However, many are now facing enormous difficulties because of rapidly rising food and fuel prices, with the threat of millions of people being pushed into poverty around the globe. The risk of continued food price volatility is a systemic challenge, and a failure in one country has been shown to have a profound impact on entire regions. This volume addresses the challenges of commodity price volatility for low-income countries and explores some macroeconomic policy options for responding to commodity price shocks. The book then looks at inclusive growth policies to address inequality in commodity-exporting countries, particularly natural resource rich countries. Perspectives from the Middle East and North Africa, sub-Saharan Africa, emerging Asia, and Mexico are presented and, finally, the role of the international donor community is examined. This volume is a must read for policymakers everywhere, from those in advanced, donor countries to those in countries with the poorest and most vulnerable populations.